Design of a planar wideband patch antenna for UHF RFID tag - Bashri, Mohd Saiful Riza; Ibrahimy, Muhammad Ibn; Motakabber , S. M. A. (Wiley Periodicals, Inc., 2014)
In this article, a planar wideband microstrip patch antenna for ultrahigh frequency (UHF) radio identification (RFID) tag is presented. By incorporating two resonating C-shape patches, two resonances are excited close to each other to create wide impedance bandwidth to cover the entire operating frequency of UHF RFID system between 860 and 960 MHz for universal mental mountable tag. For complex impedance matching between the antenna input terminal and the references microchip whose impedance is Zchip = (31-j212) Ω, a small rectangular loop feed structure was utilized where both of the resonating patches are magnetically coupled. The antenna design and simulation were carried out using finite element method based software, Ansoft HFSS v13. The simulated and measured radiation patterns at operating frequency of 915 MHz are in good agreement. the simulated and measured impedance bandwidth (Return Loss >_3 dB) of 159 and 155 MHz were obtained that are well above the required 100 MHz bandwidth.